Analisis Pengaruh Harga, Kualitas Produk Dan Kualitas Layanan Terhadap Kepuasan Konsumen Distro Nimco Di Kota Yogyakarta - Jamal Purwanto; Nonik Kusuma Ningrum; Lusia Tria Hatmanti Hutami (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine price, product quality, service quality on consumer satisfaction of Nimco Yogyakarta Distro in Yogyakarta City. This research uses a quantitative approach, the sampling method in this research was carried out by accidental sampling which is part of the nonprobability sampling technique. The population in the research is all consumers who have purchased products at the Nimco Yogyakarta Distro. The data analysis techniques used are the classical assumption test, normality test, multicollinearity test, heteroscedasticity test and multiple linear regression analysis. The hypothesis tests used are the F test (simultaneous test), T test (partial statistical test), and coefficient of determination test (R2). From the multiple linear regression analysis, the equation Y= 8.927+ 0.850 X1+ 0.474+455+ e. Simultaneous test results (F) have been carried out, resulting in Fcount being greater than Ftable (2289.776> 3.18). So it can be seen that price, product quality, and service quality have a simultaneous influence on consumer satisfaction of Nimco Distro in Yogyakarta City. And the partial test (T) produces Fcount which is greater than Ftable (X1 = 3.976 > 1.677. X2 = 4.681 > 1.677. Service has a partial influence on consumer satisfaction at Nimco Distro in Yogyakarta City. The results of this coefficient of determination show that the correlation between the independent variable and the dependent variable is R= 825a. This shows that the price and quality variables have a close relationship to consumer satisfaction at Nimco Distro Yogyakarta.